Wild mushrooms with nutritional, medicinal and biotech potential marketed in Central Valleys, Oaxaca - Jiménez Ruiz Mario; Pérez-Moreno Jesús; Almaraz-Suárez Juan J.; Torres-Aquino, Margarita (Revista Mexicana de Ciencias Agrícolas, 2018)
The edible wild mushrooms are a non-timber forest resource that has been used since pre-Hispanic times in Mexico for its high nutritional and medicinal properties. Mexico is a major reservoir of such mushrooms worldwide. In the present paper, it was identified the species of wild edible mushrooms sold in two markets of Central Valleys, Oaxaca during 2009 and 2010. Were surveyed the people collecting traditional knowledge of mushrooms marketed. 20 species of edible mushrooms were identified, ascribed to 12 genera. It was determined that these species of mushrooms have different uses, such as: i) export potential; ii) nutritional, high in protein and amino acids; iii) medicinal properties as antioxidant, anticancer, antibiotics and antitumor; and iv) biotechnological potential to produce bio inoculants, useful in forest species in Mexico. For this reason, wild edible mushrooms collected in Central Valley markets can be used fully in sustainable development models in rural communities of Oaxaca.